Impact of the COVID‐19 pandemic on hospital admissions of nursing home residents. (15th December 2021) - Tan, Li Feng; Soh, Rodney Yu Hang; Seetharaman, Santhosh Kumar
Abstract: Objective: The coronavirus disease 2019 (COVID‐19) pandemic has impacted nursing home care and activities in profound ways. We sought to understand whether the COVID‐19 pandemic had any impact on hospital admissions of nursing home residents. Methods: A retrospective analysis of hospital admissions of nursing home residents to a tertiary general hospital in Singapore during the COVID‐19 pandemic in 2020 was conducted and compared to admissions in the preceding year. Patients' demographics, length of stay, primary diagnosis on admission, death and causes of death were recorded. Results: Our study found reduced number of hospital admissions of nursing home residents to a tertiary hospital in Singapore. There was a significant decrease in pneumonia ( p < 0.001) and fall ( p = 0.001) as a primary diagnosis on admission and a decrease in pneumonia as the cause of death ( p < 0.001) for nursing home residents admitted to hospital during the COVID‐19 pandemic. Conclusions: This suggests that measures implemented during the pandemic may have impacted outcomes of nursing home residents. Further study is warranted to lead to practise changing outcomes for nursing home settings.